2021
DOI: 10.37992/2021.1202.065
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence and interrelationships for yield and yield attributing traits in horsegram

Abstract: The present experiment was carried out to estimate the genetic diversity by cluster and Principal Component analyses for seven yield and yield attributing traits in 50 horsegram germplasm accessions and two checks during the late kharif, 2019. In correlation analysis, the grain yield was positively and significantly associated with test weight and number of pods which suggested the possibilities of improving grain yield by simultaneous improvement of these traits. Using cluster analysis, the accessions were gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(9 reference statements)
1
0
0
Order By: Relevance
“…These results implied that the selection of genotypes with high mean values for a particular trait can be done and they can be employed in further crop improvement programmes. These were in accordance with the findings of Neelima et al (2021) The above study revealed the presence of wide variability among the thirty horsegram genotypes for all the traits studied. The selection for traits viz., nodes per plant, pod number per plant, seeds per pod, and 100 seed weight will be easy and would be useful in any further breeding programme for improving seed yield in horsegram.…”
Section: Swathy Sivan Et Alsupporting
confidence: 92%
“…These results implied that the selection of genotypes with high mean values for a particular trait can be done and they can be employed in further crop improvement programmes. These were in accordance with the findings of Neelima et al (2021) The above study revealed the presence of wide variability among the thirty horsegram genotypes for all the traits studied. The selection for traits viz., nodes per plant, pod number per plant, seeds per pod, and 100 seed weight will be easy and would be useful in any further breeding programme for improving seed yield in horsegram.…”
Section: Swathy Sivan Et Alsupporting
confidence: 92%